Mendamaikan Tradisi Muslim dan Ilmu Pengetahuan Modern - Nur Rofiq; M Zidny Nafi' Hasbi (INC- Islam Nusantara Center, 2021)
This paper aims to find out the results of Nidhal Guessoum's thoughts on his studies on Islam and contemporary science issues contained in his book entitled